Telomeric repeat evolution in the phylum Nematoda revealed by high-quality genome assemblies and subtelomere structures - Lim, Jiseon; Kim, Wonjoo; Kim, Jun; Lee, Junho (Genome Research, 2023)
Telomeres are composed of tandem arrays of telomeric-repeat motifs (TRMs) and telomere-binding proteins (TBPs), which are responsible for ensuring end-protection and end-replication of chromosomes. TRMs are highly conserved owing to the sequence specificity of TBPs, although significant alterations in TRM have been observed in several taxa, except Nematoda. We used public whole-genome sequencing data sets to analyze putative TRMs of 100 nematode species and determined that three distinct branches included specific novel TRMs, suggesting that evolutionary alterations in TRMs occurred in Nematoda. We focused on one of the three branches, the Panagrolaimidae family, and performed a de novo assembly of four high-quality draft genomes of the canonical (TTAGGC) and novel TRM (TTAGAC) isolates; the latter genomes revealed densely clustered arrays of the novel TRM. We then comprehensively analyzed the subtelomeric regions of the genomes to infer how the novel TRM evolved. We identified DNA damage–repair signatures in subtelomeric sequences that were representative of consequences of telomere maintenance mechanisms by alternative lengthening of telomeres. We propose a hypothetical scenario in which TTAGAC-containing units are clustered in subtelomeric regions and pre-existing TBPs capable of binding both canonical and novel TRMs aided the evolution of the novel TRM in the Panagrolaimidae family.
10.1101/gr.278124.123